Engineering Light at the Nanoscale: Structural Color Filters and Broadband Perfect Absorbers. Issue 20 (25th August 2017) - Ji, Chengang; Lee, Kyu‐Tae; Xu, Ting; Zhou, Jing; Park, Hui Joon; Guo, L. Jay
Abstract: Recent advances in fabrication and processing methods have spurred many breakthroughs in the field of nanostructures that provide novel ways of manipulating light interaction on a well controllable manner, thereby enabling a wide variety of innovative applications. Structural colors have shown great promise as an alternative for existing colorant‐based filters due to their noticeable advantages, which open up diverse potential applications such as energy‐efficient displays, ultrahigh‐resolution imaging, ultrahigh‐sensitivity biosensors, and building‐integrated photovoltaics. Broadband perfect absorbers, which exploit extraordinary optical phenomena at subwavelength scale, have also received increasing attention due to their capability of improving efficiency and performance characteristics of various applications including thermoelectrics, invisibility, solar‐thermal‐energy harvesting, and imaging. This review highlights some recent progress in these two related fields. The structural colors based on optical resonances in thin‐film structures, guided‐mode resonances in slab waveguide gratings, and surface plasmon resonances in plasmonic nanoresonators are described. Representative achievements associated with the broadband perfect absorbers, which include schemes employing highly absorbing media, multi‐cavity resonances, and broadband impedance matching are investigated. Abstract : Subwavelength nanostructures featuring extraordinary optical properties have received considerable research interest in the field of structural color filters and broadband perfect absorbers due to their unique advantages over conventional counterparts. This review summarizes recent work in these areas with a detailed discussion of design principles, characteristic performances, implementation approaches, and practical applications, aiming to inspire further investigations in nanotechnology.